Radiation and Hygiene Assessment of the Consequences of Nuclear Tests at the Semipalatinsk Test Site - Nikolay Meshkov (Journal of Global Pharma Technology, 2020)
The analysis of the spatial and intra-profile distribution of cesium-137 (137Cs) reserves in the soils of the Altai Mountains, as well as the dynamics of the specific activity of this radionuclide in food products produced in the territory of the Republic of Altai and the Altai territory, in 1966-1985, was performed. Individual annual effective doses of internal radiation of the adult population of the Republic of Altai and the Altai territory due to the receipt of 137Cs with food were calculated and a forecast of long-term radiological consequences for the population of the Republic of Altai was made. Keywords: Radioactivity; Radio nuclides; Cesium-137; Semipalatinsk.